PERLINDUNGAN HUKUM BAGI PASAR TRADISIONAL DI ERA GLOBALISASI DAN LIBERALISASI PERDAGANGAN - Marcel Seran (Faculty of Law, Universitas Diponegoro, 2014)
Globalization and trade liberalization have penetrated territorial limits of countries in the world, and affected on peoples lives i.e. order on aspect of political, economic, social, cultural and legal. Indonesia as one part of the world community is not to escape from that influence.The influx of investments in modern market of Indonesia is evidence of this influence. However, with the influx of investments in modern markets has also led to the beginning of marginalization of traditional markets.Therefore, there is a need for legal protection for the traditional market in order that it flourishes side by side with modern markets; it can also be strategic partners in support of economic development towards a just and prosperous society based on Pancasila and the 1945 constitution